Synthesis and Dehydrogenation of Isoxazolines by Using DMSO-I2-H2SO4 and DMSO-I2 System - Deshmukh, A.Y.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
4´-Chlorochalcone (Ia), 4´-chloro-4-methoxychalcone (Ib), 4´-nitrochalcone (Ic) and 4´-nitro-4-methoxychalcone (Id) have been condensed with hydroxylamine hydrochloride to yield isoxazolines (IIa–d). Isoxazolines (IIa–d) have been suspended in DMSO and crystals of iodine to yield isoxazoles (IIIa–d).